Driving Force for Change Statewide 2018 Annual Report - Floros, John D. (My University, 2018)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2018, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN32_2018_01
Keywords: UNN32; Administrative and Research Reports; legislature